eSports Venues: A New Sport Business Opportunity - Seth E. Jenny; Margaret C. Keiper; Blake J. Taylor; Dylan P. Williams; Joey Gawrysiak; R. Douglas Manning; Patrick M. Tutka (Journal of Applied Sports Management, 2018)
Typically played via the Internet, eSports (organized competitive video gaming) is becoming a global phenomenon. The popularity of video games and the desire to spectate online and in-person gaming has amplified as Internet-based gaming has improved. eSports competitions are hosted all around the world, but particularly in the United States, Europe, and Asia. While eSports-specific venues are increasingly being built, many venues that host eSports competitions were constructed primarily for other professional sports or entertainment. These entertainment facilities must attract popular financially beneficial events in order to survive. eSports events have great potential to fit this mold. This paper briefly describes the development of eSports as well as discusses the current trends in eSports spectator consumption. Moreover, current and future eSports venues are described, highlighting potential licensing, equipment, and personnel requirements needed for hosting eSports events. Open systems theory is utilized to capture and explain the draw of hosting eSports events and how facilities must adapt to their changing environment. Subscribe to JASM
Keywords: e-Sports; video gaming; electronic sports; sport venues; facilities